2018
DOI: 10.1111/cbdd.13450
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of MT1‐MMP cell surface‐associated activity

Abstract: Quantitative assessment of MT1‐MMP cell surface‐associated proteolytic activity remains undefined. Presently, MT1‐MMP was stably expressed and a cell‐based FRET assay developed to quantify activity toward synthetic collagen‐model triple‐helices. To estimate the importance of cell surface localization and specific structural domains on MT1‐MMP proteolysis, activity measurements were performed using a series of membrane‐anchored MT1‐MMP mutants and compared directly with those of soluble MT1‐MMP. MT1‐MMP activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 102 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…The collagenolytic activity of MMP-14 on the cell surface is enhanced predominantly by its hemopexin domain-dependent homodimerization [ 124 ]. It is regulated by interactions with integrins, CD44, chondroitin/heparin sulfate proteoglycans, tetraspanins, pericellular MMP-14-inhibiting proteins TIMP-2, -3, and -4, and RECK [ 158 , 170 , 171 , 172 ]. The O-glycosylation pattern also determines the lifespan of MMP-14 and, thus, the invasiveness of cancer cells [ 173 ].…”
Section: Molecular Biology Of Mmpsmentioning
confidence: 99%
“…The collagenolytic activity of MMP-14 on the cell surface is enhanced predominantly by its hemopexin domain-dependent homodimerization [ 124 ]. It is regulated by interactions with integrins, CD44, chondroitin/heparin sulfate proteoglycans, tetraspanins, pericellular MMP-14-inhibiting proteins TIMP-2, -3, and -4, and RECK [ 158 , 170 , 171 , 172 ]. The O-glycosylation pattern also determines the lifespan of MMP-14 and, thus, the invasiveness of cancer cells [ 173 ].…”
Section: Molecular Biology Of Mmpsmentioning
confidence: 99%
“…However, the appearance of a corresponding band in the zymogram analysis indicated ability to cleave gelatin and suggested that this specific auto-processing by initial KLK14-mediation may be responsible for shedding of the active catalytic domain of MMP15 from the cell surface ( Figure 4 C). Interestingly, the cell surface localization of MMP15 was essential for its ability to cleave collagen in cell-based assays, and it was required for exhibition of invasive cancer cell phenotypes [ 36 , 37 ], while soluble MMP15 was found to display a nearly 13-fold higher activity on triple-helical substrates compared to the cell-surface located form [ 38 ]. This suggests, that release of the mature MMP15 from the cell surface may be an important regulatory step, resulting in enhanced triple helical collagen I degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cell surface localization of MMP15 was essential for its ability to cleave collagen in cell-based assays and it was required for exhibition of invasive cancer cell phenotypes [34], [35], while soluble MMP15 was found to display a nearly 13-fold higher activity on triple-helical substrates compared to the cell-surface located form [36]. This suggests, that release of the mature MMP15 from the cell surface may be an important regulatory step, resulting in enhanced triple helical collagen I degradation.…”
Section: Discussionmentioning
confidence: 99%